The Effect of Using NPK Fertilizer and Liquid Organic Fertilizer Vegetable Waste on the Vegetative Growth of Purple Eggplant (Solanum melongena L.) - Aryani, Maesa; Raksun, Ahmad; Mertha, I Gde (Jurnal Biologi Tropis, 2024)
An key factor in promoting the growth and development of plants is fertilizer. Both organic and inorganic fertilizers can be used for fertilization. If inorganic fertilizers are applied over an extended period of time without the incorporation of organic matter, the soil's quality may be compromised, leading to suboptimal plant development. The purpose of this study is to ascertain the optimal fertilizer dose for purple eggplant growth response, as well as the effects of NPK fertilizer, liquid organic fertilizer made from vegetable waste, and a combination of both on the vegetative growth of purple eggplant plants. A two-factor Complete Random Design was employed in this study, with three replicates and five treatment levels for each of the liquid organic fertilizer made from vegetable waste and NPK fertilizer treatment. The Anova two-way test was used to examine the data, and then the DMRT test was performed. The application of liquid organic fertilizer made from vegetable waste and the combination of the two fertilizers had a real effect on plant height, leaf area, wet weight, and dry weight but no real effect on the number of leaves, according to the results. On the other hand, the application of NPK fertilizer had a real effect on plant height, number of leaves, leaf area, wet weight, and dry weight. The results of the DMRT test (5%) indicated that the optimal dosage for plant height, wet weight, and dry weight was 1.5 grams of NPK and 10 ml of liquid organic fertilizer made from vegetable waste; for the number of leaves, it was 1.5 grams of NPK and 2 grams, and for the area of leaves, it was 1 gram of NPK.